Potensi tumbuhan keluak (Pangium edule Reinw) sebagai sumber antioksidan, antimikroba, dan aplikasinya dalam bidang pangan: a short review - Muhammad Yunus; Krishna Purnawan Candra; Marwati Marwati (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Keluak is a multi-purpose plants whose plant part (seeds and leaves) function as herbal medicine. This narrative review aims to reveal the potential of the keluak plant as a source of antioxidants, antimicrobials and its application in the food sector. The literature search method using the Boolean technique is used by combining several keywords with the AND, OR, NOT notations from several kinds of literature, both national and international journals, published from various databases. Various potential antioxidant compounds found in seeds, leaves, keluak fruit are Vitamin E, Vitamin C, polyphenols, saponins, steroids, phenolics, tannins, flavonoids (quercetin and catechins), quinine, and β-carotene. Various bacteria whose growth can be inhibited by extracts/materials from seeds, leaves, and fruit of keluak are Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus cereus, Morganella morganii, Microbacterium testaceum, Raoultella terigena, Salmonella typhimurium, Listeria monocytogenes, Enterobacteriaceae, and viruses SARS CoV 2. Seeds and leaves of the keluak plant have the potential to be developed as antioxidant and antimicrobial agents in commercial dosage forms such as natural food preservatives that are safe to use in food ingredients and processed food products.